A Educação Musical na formação em Dança: propriedades e particularidades - Camila de Queiroz (2013)
This dissertation is focused on how music is taught in a São Paulo States academic dance course. After a brief study on the specific legislation (Curricular Policies), I present some information about the interaction between the music and the dance arts, including the relevance of music education for dance students. Then, I introduce reports from a field research that indicates how these students connect with music, which are their difficulties and needs, and how music education is placed in the dance academic course.